Understorey biodiversity management in olive groves for integrated management of natural enemies - Stavrianakis, Georgios; Stattegger, Sophie Rosa; Sentas, Efstratios; Tsamakda, Aikaterini; Grumic, Ioannis; Tscheulin, Thomas; Kizos, Athanasios (ENTOMOLOGIA HELLENICA, 2023)
The management of natural enemies of perennial tree crops and especially insects is usually performed with pesticides, which can negatively impact the quality of products, natural resources, and biodiversity as well as the health of producers and consumers. An emerging trend focuses alternatively on the use of less or no chemicals and the management of crop pests with natural means. This trend is being promoted by the European Union through the new Common Agricultural Policy. Olive cultivation is one of the most important permanent crops in the Mediterranean area. The most important pest in olive groves is the olive fly [Bactrocera oleae (Rossi) (Diptera: Tephritidae)]. In this study we investigate the relationship between the fly population and plant and insect diversity in the understorey of 15 fields on Lesvos Island during 2021 and 2022. The results suggest that maintaining the plant cover undisturbed significantly improves the biodiversity of the olive groves and by extension the ecosystem services, such as pollination, pest control and soil health.